Hydrothermal Alteration And Vein Types Of The Randu Kuning Porphyry Cu-Au Deposit At Selogiri Area, Wonogiri - Sutarto, Sutarto; Idrus, Arifudin; Putranto, Sapto; Harjoko, Agung; Setijadji, Lucas D; Meyer, Franz M; Danny, Rama (Buletin Sumber Daya Geologi, 2014)
Many Tertiary hydrothermal altered dioritic composition intrusive rocks were found at the Randu Kuning  area and its vicinity, Selogiri, including hornblende microdiorite, hornblende-pyroxene diorite and quartz diorite. The hydrothermal fluids which responsible for the alteration and mineralization at the area is associated with the occurence of the horblende microdiorite intrusion.The alteration zone at the Randu Kuning area and its vicinity can be divided into several hydrothermal alteration zones, such as potassic (magnetite-biotite-K feldspar), prophyllitic (chlorite-magnetite-epidote-carbonate), phyllic (quartz-sericite-chlorite) and argillic (clay mineral-sericite). The alteration pattern in the Randu Kuning porphyry Cu-Au deposit is tipically a diorite  model characterising by the domination of  potassic alteration and prophyllitic zone. Phyllic and argillic alteration types are  restrictive found within the fault zones.A lot of porphyry vein types were found and observed at the Randu Kuning area, and classified into at least seven  vein types.  The paragenetic sequence of those veins from the earliest to the latest respectively are 1). Magnetite-chalcopyrite±quartz-biotite veinlets, 2). Quartz±magnetite (A type) veins, 3). Banded/Laminated quartz-magnetite (M type) veins, 4). Quartz±K feldspar (B type)veins, 5). Quartz  with thin centre line sulphide (AB type) veins, 6). Pyrite±chalcopyrite (C type) veinlets, and 7). Pyrite-quartz+chalcopyrire+carbonate (Dtype) veins. Gold and copper mineralisation  of the Randu Kuning Porphyry Cu-Au deposit, mostly related to the presence of quartz veins/veinlets containing sulfide i.e. Quartz  with thin centre line sulphide veins, Pyrite±chalcopyrite veinlets, and Pyrite-quartz+chalcopyrire+ carbonate veins.